2014
DOI: 10.1093/arclin/acu003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Aquatic Exercise Program on Inhibitory Control in Children with ADHD: A Preliminary Study

Abstract: The purpose of this preliminary study was to examine whether an aquatic exercise intervention that involves both aerobic and coordinative exercises influences restraint inhibition in children with ADHD. Thirty participants were assigned to either an aquatic exercise or a wait-list control group. Participants were assessed by Go/Nogo Task and motor ability prior to and after an 8-week exercise intervention (twice per week, 90 min per session) or a control intervention. Significant improvements in accuracy assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 19 publications
7
106
1
6
Order By: Relevance
“…Two students withdrew from the physical activity group in the program's first week, while two others were expelled from the attention control group and one from the physical activity group for repeated serious infractions (e.g., cursing, hitting, throwing furniture) over the course of the program. Previous studies of physical activity for children with ADHD have reported retention rates between 86% and 90% (7, 8, 21), which is in line with the rate observed in the current study. Few after-school alternatives were available in the participating neighborhood, however, roughly 1 in 5 children enrolled in other after-school programs on one or two days per week.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Two students withdrew from the physical activity group in the program's first week, while two others were expelled from the attention control group and one from the physical activity group for repeated serious infractions (e.g., cursing, hitting, throwing furniture) over the course of the program. Previous studies of physical activity for children with ADHD have reported retention rates between 86% and 90% (7, 8, 21), which is in line with the rate observed in the current study. Few after-school alternatives were available in the participating neighborhood, however, roughly 1 in 5 children enrolled in other after-school programs on one or two days per week.…”
Section: Discussionsupporting
confidence: 92%
“…That said, longitudinal studies conducted with children with ADHD and DBD often demonstrate trajectories of escalating problem severity with regard to inattention, conduct, and oppositional defiance when untreated (2, 4) and quasi-experimental studies in ADHD have shown little to no improvement in no-intervention control groups on cognitive and behavioral symptom outcomes in children (7, 55). Both groups received daily homework support, which may have been responsible for a portion of program benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 8 unique studies (Bustamante, et al, 2016;Chang, Hung, Huang, Hatfield, & Hung, 2014;Choi, Han, Kang, Jung, & Renshaw, 2015;Janssen, et al, 2016;Jensen & Kenny, 2004;Kang, Choi, Kang, & Han, 2011;Lee, Lee, & Park, 2015;Meßler, Holmberg, & Sperlich, 2016) were included in the meta-analysis. One study included two physical activity arms.…”
Section: Study Selectionmentioning
confidence: 99%
“…The few existing intervention studies mostly reveal positive effects on cognitive performance [3541], whereby multimodal treatment methods in particular are attributed with a greater efficacy and broader transfer effects (also to health and well-being). In this context, qualitative characteristics of the physical activity, such as adaptiveness to the individual performance level and cognitive demands, are attributed with playing a central role [42].…”
Section: Introductionmentioning
confidence: 99%